Presenting the entrepreneurial school model in Iran - tayebeh shahrostambeig; esmat Masoudi Nadushan; zahra taleb (مدیریت و چشم انداز آموزش)
Abstract The aim of the current research is to present the entrepreneurial school model. The research method is applicable in terms of purpose, and quantitative in terms of implementation. The statistical population includes 102 experts and specialists and professors of Iranian universities in the field of entrepreneurship, and the purposeful sampling method was used for sampling. Data collection is done using a researcher-made questionnaire. Data analysis was done using SPSS and PLS software. The results of the research showed that the components obtained from the qualitative part for the category of "entrepreneurial school" have 8 dimensions and 60 themes. The dimensions are: causal factors: (1- management), strategies: (2- teaching-learning strategies), consequences: (3- goals), contextual factors: (4- educational tools), 5- entrepreneurial content, 6- contextual conditions), intervening factors: (7- evaluation, 8- quality of professors). Also, the GOF value is equal to 0.645, which indicates a strong model fit. Extended abstract Introduction Today, economic and social changes and developments have made the need for effective education necessary. Therefore, schools have a special place and importance at the top of the education system as an institution for educating students with entrepreneurial and innovative thinking who can create value in the society. On the one hand, according to the researches, entrepreneurial opportunities in developing countries such as Iran are seven times more than that of developed countries; and on the other hand, the inefficiency of formal education for reasons such as low quality and inflexibility of the country's education system according to the current needs of the community and the increase in unemployment of graduates due to the lack of skill-oriented empowerment, doubles the movement towards the generation of entrepreneurial schools (Fathy karkaragh et al, 2021). The entrepreneur school is one of the structural changes of the emerging phenomenon at the level of public education, which is proposed with the aim of training students to play an entrepreneurial role in the society. In such schools, the roles and responsibilities of all school stakeholders, including the principal, teacher, and student, as well as the nature of the curriculum and even the expectations of parents and the larger society, require redefinition (Haji Aghaee & Khalkhali, 2021). The entrepreneur school is a school that, in addition to theoretical training, teaches social abilities, communication skills, creative approaches, etc. by holding various classes and workshops. Such a school supports teachers and guides them to improve their performance. In addition to influencing the bosses, the manager has independence in his thoughts and actions. In a healthy school, students participate in scientific activities with high motivation, educational tools and educational assistance are available to them, and finally, teachers love each other, trust each other, and are compassionate in their work (Moradian et al, 2021). Therefore, based on the said material, the researcher is trying to answer the question: what is the design of the entrepreneurial school model? Theoretical Framework Entrepreneurial schools Entrepreneurial schools are established with the aim of producing knowledge and applying it to the development of different sectors of society through research, education and production. Entrepreneurial schools emphasize the opportunities for innovation, growth and development. In these schools, creativity is encouraged and strengthened throughout the organization to maintain the entrepreneurial culture (Deveci & Seikkula-Leino, 2018). Entrepreneurial schools, by creating a culture of improvement in the school and collaboration culture among employees, focus on better learning to achieve learning goals through creative and innovative learning methods, focusing on entrepreneurship goals related to national strategies and action plans, local curriculum in entrepreneurship, future vision of students, vision of student identity and vision Students on learning (Ghafrani et al, 2022). Entrepreneurship Entrepreneurship is a word that has really attracted the attention of researchers since 1960. In the early definitions of economists, they focused on providing functional definitions and dimensions of economic growth and profitability, and then psychologists studied the individual psychological characteristics of entrepreneurship. And finally, sociologists, believing that the inner motivation of entrepreneurship is its driving force, which is strengthened from childhood by being influenced by the surrounding environment, investigated the dimensions and social consequences of entrepreneurship (Ahmadpour Dariani, 2018). Mashrouhi Fard et al, (2023) investigated the modeling of factors influencing the creation of an entrepreneurial school in elementary school. The results of the qualitative part showed that the model of creating entrepreneurial schools in the elementary school included 8 factors. Based on the results of the confirmatory factor analysis, two indicators were removed from the total of 58 components that were categorized into 8 main factors, and 56 indicators were confirmed. Therefore, the entrepreneurial school model was obtained in the elementary school with 56 components that were categorized into 8 main factors. In recent years, the development of entrepreneurship in schools has been placed on the agenda of education. The results of this study can help policymakers and education professionals in the development of entrepreneurial schools. Ghafrani et al, (2022) investigated the design of entrepreneurial schools model focusing on the development of entrepreneurial skills of secondary school students. The resulting paradigm model was formed based on the central phenomenon (entrepreneurial competence) affected by causal conditions, background conditions and intervening variables along with action and reaction strategies and the consequences of creating entrepreneurial schools in the secondary level. Research methodology The research method is applicable in terms of purpose, and quantitative in terms of implementation. The statistical population includes 102 experts and specialists and professors of Iranian universities in the field of entrepreneurship, and the purposeful sampling method was used for sampling. Data collection is done using a researcher-made questionnaire. Research findings Data analysis was done using SPSS and PLS software. The results of the research showed that the components obtained from the qualitative part for the category of "entrepreneurial school" have 8 dimensions and 60 themes. The dimensions are: causal factors: (1- management), strategies: (2- teaching-learning strategies), consequences: (3- goals), contextual factors: (4- educational tools), 5- entrepreneurial content, 6- contextual conditions), intervening factors: (7- evaluation, 8- quality of professors). Also, the GOF value is equal to 0.645, which indicates a strong model fit. Conclusion The present research was conducted with the aim of presenting the entrepreneurial school model. These results of this research are in agreement with the results of Mashrouhi Fard et al, (2023), Ghafrani et al, (2022), Nasiri et al, (2022), Fathy karkaragh et al, (2021), Haji Aghaee & Khalkhali (2021), Nasiri Valikbani & Ghaderi sheykheeabadi (2021), Samkange (2020), Tshehla (2019), Ristovska & Stankovska (2019), and Kirkley (2017). Samkange (2020) showed that teachers still rely on traditional teaching methods and do not develop innovative thinking that is critical in developing entrepreneurial skills. It was also pointed out that schools lacked programs that could be described as entrepreneurship education. He believed that entrepreneurship education should be designed as a subject in the school curriculum. According to the results of this research, it is suggested: Since one of the dimensions of entrepreneurship education is teaching-learning strategies, various educational methods such as writing business plans and practical projects, educational workshops, storytelling, games at pre-primary and elementary school levels, and scientific visits should be used according to the needs and interests of the learners. Education and training and professional development of entrepreneurial teachers and professors, who have a positive attitude and are committed to the development of entrepreneurship and have the necessary scientific ability, knowledge and skills, should be taken into consideration in the centers related to the recruitment, cultivation and evaluation of entrepreneurial human resources.